2005
DOI: 10.1021/jp050558z
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Ti-Catalyzed Hydrogen Chemisorption on an Al Surface:  A Critical First Step for Reversible Hydrogen Storage in NaAlH4

Abstract: Complex metal hydrides are perhaps the most promising hydrogen storage materials for a gradual transformation to a hydrogen-based economy. We have used a computational approach to aid the ongoing experimental effort to understand the reversible hydrogen storage in Ti-doped NaAlH(4) and propose a plausible first step in the rehydrogenation mechanism. The study provides insight into the catalytic role played by the Ti atoms on an Al surface in the chemisorption of molecular hydrogen and identifies the local arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
107
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 23 publications
10
107
0
Order By: Relevance
“…The role of Ti dopant in the latter case has been recently identified as catalytic role on Al surface in the chemisorption of molecular hydrogen. 40 Here we have demonstrated that two Al-H bond lengths will become elongated and weakened due to the presence of a Na vacancy on the NaAlH 4 ͑001͒ surface. Spontaneous recombination from the surface to form molecular hydrogen is observed in the spin-polarized ab initio molecular dynamics simulation.…”
mentioning
confidence: 70%
“…The role of Ti dopant in the latter case has been recently identified as catalytic role on Al surface in the chemisorption of molecular hydrogen. 40 Here we have demonstrated that two Al-H bond lengths will become elongated and weakened due to the presence of a Na vacancy on the NaAlH 4 ͑001͒ surface. Spontaneous recombination from the surface to form molecular hydrogen is observed in the spin-polarized ab initio molecular dynamics simulation.…”
mentioning
confidence: 70%
“…13,17 TiAl 3 has two possible structures: cubic L1 2 and tetragonal D0 22 . 19 We will examine Ti positions following both arrangements near an Al(001) surface.…”
Section: Calculational Detailsmentioning
confidence: 99%
“…We do not find any favorable active Ti sites on the surface as considered in previous studies. 13,22,23 The result is understandable since the Al surface has a lower surface energy than the Ti surface, so exposing Ti atoms raises the energy. A surface reconstruction induced by the presence of Ti in the topmost surface layer was proposed in Ref.…”
Section: Calculational Detailsmentioning
confidence: 99%
“…In two papers [168,169], Chaudhuri and Chopra et al demonstrated that aluminum doped with very small amounts of Ti can activate molecular H 2 at temperatures as low as 90 K. In the earlier work, Chaudhuri et al showed using first-principles techniques that a particular local arrangement of Ti atoms is responsible for catalyzing the chemisorption of molecular hydrogen on TiAl surfaces. The subsequent work by Chopra et al published 6 years later extended the earlier first-principles calculations.…”
Section: Catalysts For Production and Activation Of Hmentioning
confidence: 99%